(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the theoretical foundations of modern pedagogical technologies in the process of forming independence in children. Independence means the development of such personal qualities as the child’s ability to freely express his opinion, make decisions, and feel responsibility. The article reveals the factors affecting the formation of independence, in particular, the didactic capabilities of information and communication technologies (ICT), interactive methods, digital learning platforms, and multimedia tools. Special attention is also paid to the development of children’s independent thinking, problem-solving, and self-control skills using modern technologies. Based on the results of the research, scientific and methodological recommendations for the integration of modern technologies into children’s education have been developed.